KEBIJAKAN REFORMA AGRARIA TERHADAP LAHAN PERTANIAN DI KABUPATEN TULUNGAGUNG - Siti Chadijah; Dwi Kusumo Wardhani; Ali Imron (STIH Putri Maharaja, 2020)
The phenomenon of agricultural land use change one of which occurred in Tulungagung Regency, East Java. Agricultural land in Tulungagung Regency continues to experience shrinking, triggering fears of instability in the area's food security. Thus this research aims to answer and describe how: (1) Implementation of policies on agricultural land in Tulungagung Regency and (2) Factors that influence the implementation of agrarian reform in the Tulungagung Regency. The analysis begins dissecting the laws and regulations relating to Agrarian and Agrarian Reform Policies, among others: UUPA, Perpres No. 86 of 2018 on Agrarian Reform, and is associated with regulations related to the control and use of agricultural land, among others; Law No. 41 of 2009 concerning Protection of Sustainable Agricultural Land. Furthermore, reviewing the regulations at the Tulungagung District Land Office related to the Agrarian Reform on the Control and Use of Agricultural Land and Regional Regulations in force, then photographing how they are applied in the field so as to draw conclusions from the factors that influence the implementation of Agrarian Reform, one of which is a change use of agricultural land to become non-agricultural. The results of the study concluded that a strategic step is needed in the form of food agricultural land protection in Tulungagung Regency by regulating and immediately establishing it as a Sustainable Food Agriculture Area.